Body composition of elite soccer players from Montenegro and Kosovo - Gardasevic, J.; Bjelica, D.; Vasiljevic, I.; Arifi, F.; Sermaxhaj, S. (SportMont, 2019)
A soccer game is said to be the most important "secondary thing" in the world; it gathers huge masses at stadiums and in front of TVs (Gardasevic, Bjelica, & Vasiljevic, 2019). It is a highly dynamic and fast team game that, with its richness of movement, falls under the category of polystructural sports games (Gardasevic, Bjelica, & Corluka, 2018; Bjelica, Popovic, Gardasevic, & Krivokapic, 2016). Soccer is a sport that is characterized by numerous and various complex and dynamic kinesiological activities, which are then characterized by either cyclical (Sermaxhaj, Popovic, Bjelica, Gardasevic, & Arifi, 2017; Gusic, Popovic, Molnar, Masanovic, & Radakovic, 2017; Gardasevic, Bjelica, & Vasiljevic, 2017) or acyclical movement (Masanovic, 2019; Masanovic, T. Bavcevic, & I. Bavcevic, 2019; Gardasevic, Bjelica i Vasiljevic, 2016; Gardasevic, Bjelica, Milasinovic i Vasiljevic, 2016; Gardasevic, Popovic, & Bjelica, 2016). In sport, top scores can be achieved only under conditions of well-programmed training process (Gardasevic, Akpinar, Popovic, & Bjelica, 2019; Gardasevic & Bjelica, 2019; Bjelica, Popovic, Tanase, & Gardasevic, 2017; Bojanic, Petkovic, Gardasevic, Muratovic, & Vasiljevic, 2015). High quality management of the training process depends on knowing the structure of specific anthropological capabilities and players` characteristics, as well as their development (Arifi, Bjelica, & Masanovic, 2019; Masanovic, 2018; Bjelica & Gardasevic, 2018; Bjelica, Popovic, & Gardasevic, 2016a; Bjelica, Popovic, & Gardasevic, 2016b).